Amenaza de contaminación del agua subterránea en el sector norte del acuífero Barva, Heredia, Costa Rica - Madrigal-Solís, Helga (2014)
Most of the water for human consumption and the development of economic activities in the Central Valley of Costa Rica is supplied by the aquifers located in this region. Nevertheless, many of these activities are located in the recharge area of the Barva free aquifer, representing a threat to the quality of the water. The objective of this study was to develop a pollution load map for the municipalities of Santa Barbara, Barva and San Rafael, in Heredia, Costa Rica, as a first step towards generating a risk map for the Barva aquifer. To this end, the activities in this region were identified, located and classified using the POSH method (commonly known as "Pollutant Origin and Surcharge Hydraulically"). Then, the area was divided into 250 x 250 m cells and each received the maximum potential pollutant load according to the value assigned to the sources in the cell. Forty-five percent of the 2103 cells were found to contain at least one activity with a high potential for generating a pollutant load, 32% contained at least one activity with a moderate potential, 14% had at least one activity with a low potential and 9% did not have any activity with the potential of generating a pollutant load. In addition, the Bambinos and Los Angeles sub-aquifers were identified as the most critical sectors. The information generated will contribute to the design and implementation of stricter control measures aimed at minimizing the probability of pollution.